2014
DOI: 10.1016/j.scitotenv.2013.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Ozonation of wastewater: Removal and transformation products of drugs of abuse

Abstract: • The ozonation of six drugs of abuse and one human drug metabolite was carried out.• Drug removals vary between 3 and 50% for the ozone doses tested.• The main transformation products of the drugs of abuse were identified.• The most plausible structure of a transformation product of MDMA was elucidated. a b s t r a c t a r t i c l e i n f o In this study amphetamine, methamphetamine, methylenedioxymethamphetamine (MDMA), cocaine (COC), benzoylecgonine (BE), ketamine (KET) and oxycodone (OXY) in wastewater at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 68 publications
2
21
1
Order By: Relevance
“…In the present study, we showed that ozonation treatment is efficient at removing the four target hormones at concentrations below their limit of detection. This is in accordance with what we, and others, have previously shown for the removal of hormones and other drugs [6,31]. We had previously described that the O 3 treatment of EE2 at higher initial concentration (50 -500 μg/L) leads to the production of 2 transformation products [6].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we showed that ozonation treatment is efficient at removing the four target hormones at concentrations below their limit of detection. This is in accordance with what we, and others, have previously shown for the removal of hormones and other drugs [6,31]. We had previously described that the O 3 treatment of EE2 at higher initial concentration (50 -500 μg/L) leads to the production of 2 transformation products [6].…”
Section: Discussionsupporting
confidence: 92%
“…Chromatographic separation and analysis in positive ion 236 mode was achieved using the methods described by Rodayan et al (2014b). Acquisition was 237 performed in full scan mode (50-400 m/z) at high resolution (RFWHM = 41,000).…”
mentioning
confidence: 99%
“…ozonation, O 3 /UV, O 3 /H 2 O 2 , ultrafiltration, reverse osmosis, granular activated carbon and membrane biological reactors) to facilitate the removal of organic pollutants from influents. [75][76][77][78][79][80][81] In addition, the removal of pharmaceuticals in wastewater is being examined through the application of other technologies such as constructed wetlands, surface flow systems (lagoons or anaerobic or facultative ponds), horizontal subsurface flow systems, and vertical subsurface flow systems. [76,80] Opioids…”
Section: Chemicalmentioning
confidence: 99%